Chemical and antioxidant activity changes in Philippine green mussel (Perna viridis) during fermentation at varying salt concentrations - Peralta, Ernestina M.; Endoma, Leonilo F.; Sefil, Ariel S.; Palmos, Grace N. (2021)
"Green mussel (Perna viridis) is an extensively cultured bivalve species in the Philippines and a cheap source of valuable nutrients such as essential amino acids and minerals. Experimental samples were prepared by mixing salt to varying mussel meat ratios (1:3, 1:5, 1:7, and 1:9) which were assessed for changes in pH, degree of hydrolysis, and antioxidant activities during fermentation for 30 d." - Abstract.
Includes bibliographical references.
Keywords: Perna viridis -- Philippines; Fermented foods -- Philippines